A Cross-Tissue Transcriptome-Wide Association Study Identifies Novel Susceptibility Genes for Juvenile Idiopathic Arthritis in Asia and Europe - Xu, Jiawen; Ma, Jun; Zeng, Yi; Si, Haibo; Wu, Yuangang; Zhang, Shaoyun; Shen, Bin (Frontiers in Immunology, 2022)
Abstract Background: Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in children, and its pathogenesis is still unclear. Genome-wide association studies (GWASs) of JIA have identified hundreds of risk factors, but few of them implicated specific biological mechanisms. Methods: A cross-tissue transcriptome-wide association study (TWAS) was performed with the FUSION tool based on GWAS summary datasets (898 JIA patients and 346,102 controls from BioBank Japan (BBJ)/ FinnGen). The gene expression reference weights of skeletal muscle and the whole blood were obtained from the Genotype-Tissue Expression (GTExv8) project. JIA related genes identified by TWAS findings genes were further compared with the differentially expressed genes (DEGs) identified by the mRNA expression profile of JIA from the Gene Expression Omnibus (GEO) database (accession number: GSE1402). Last, candidate genes were analyzed using functional enrichment and annotation analysis by Metascape to examine JIA-related gene sets. Results: The TWAS identified 676 significant genes with P values < 0.05 and contains 373 for Asia and 303 for Europe, such as CDC16 (P = 1.72E-03) and PSMD5-AS1 (P = 3.65E-02). Eight overlapping genes were identified based on TWAS results and DEGs of JIA patients, such as SIRPB1 (PTWAS = 4.21E-03, PDEG = 1.50E-04), and FRAT2 (PTWAS = 2.82E-02, PDEG = 1.43E-02). Pathway enrichment analysis of TWAS identified 183 pathways such as cytokine signaling in the immune system and cell adhesion molecules. By integrating the results of DEGs pathway and process enrichment analyses, 19 terms were identified such as positive regulation of T-cell activation. Conclusion: By conducting two populations TWAS, we identified a group of JIA-associated genes and pathways, which may provide novel clues to uncover the pathogenesis of JIA.